A Comparative Study on Phytochemical Fingerprint of Two Diverse Phaseolus vulgarisvar. Tondino del Tavo and Cannellino Bio Extracts - Azzurra Stefanucci; Giuseppe Scioli; Lorenza Marinaccio; Gokhan Zengin; Marcello Locatelli; Angela Tartaglia; Alice Della Valle; Angelo Cichelli; Ettore Novellino; Stefano Pieretti; Adriano Mollica (MDPI AG, 2022)
Common bean (Phaseolus vulgaris) represents one of the most famous foods with antiobesity activity showing a significant efficacy against fat accumulation, insulin resistance and dyslipidaemia. In this work, two Italian varieties of common bean, i.e., Tondino del Tavo and Cannellino Bio, from the centre of Italy were studied to characterise their phenolic profile by HPLC-PDA in relation to different fractions after a straightforward extraction procedure. Antioxidant property and enzymatic inhibition power were also evaluated in order to delineate a possible biological profile. Results show a considerable phenolic content (0.79 and 1.1 µg/mg of 3-hydroxybenzoic acid for hexane extract of Tondino del Tavo and Cannellino Bio, respectively; 0.30 µg/mg p-coumaric acid for n-hexane extract of Tondino del Tavo) for both varieties, and a strong antioxidant activity according to the major phenolic concentration of the extracts. The anti-inflammatory activity of the decoction extracts was also investigated through a zymosan-induced edema formation assay, revealing a moderate ability for both of them. These preliminary data prompt us to further explore the nutrient components of these two varieties in the future.